The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1086/505642
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Coronal Loop Oscillations by Random Energy Releases

Abstract: High-resolution observations by the SOHO and TRACE spacecraft have confirmed the existence of coronal loop oscillations and waves. In a recent work, Mendoza-Briceño et al. studied the heating response of coronal plasma to energy pulses randomly distributed in time and space along coronal loops. In this paper we focus on the oscillatory patterns and other features, such as cool gas blobs traveling along the loop, during the evolution of spatiotemporal randomly heated flux tubes in the corona. The nature of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Mendoza-Briceño et al (2006) reported for this case a period of about 180 s, coming from a wavelet analysis of their time series, which matches well with this calculation. This might be and indication that the fundamental slow mode is being excited in their model, even if its spatial structure is not evident in their simulations due to the propagation, dissipation and nonlinear effects considered in their calculations.…”
Section: Slow Modes Of An Averaged Density Equilibrium Generated By Rsupporting
confidence: 88%
See 2 more Smart Citations
“…Mendoza-Briceño et al (2006) reported for this case a period of about 180 s, coming from a wavelet analysis of their time series, which matches well with this calculation. This might be and indication that the fundamental slow mode is being excited in their model, even if its spatial structure is not evident in their simulations due to the propagation, dissipation and nonlinear effects considered in their calculations.…”
Section: Slow Modes Of An Averaged Density Equilibrium Generated By Rsupporting
confidence: 88%
“…We deduce that it is not only important the total amount of material in the loop, but also its distribution. We can compare our analytical work with results obtained from 1D numerical simulations by Selwa et al (2005) and Mendoza-Briceño et al (2006), since the only comparison in these works was done with the results for a homogeneous loop. The hyperbolic density profile used in Selwa et al (2005) has a high density contrast between the footpoints and the apex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One-dimensional calculations of time-dependent plasma behavior in response to impulsive heating just above the chromosphere were reported recently by Testa et al (2005) and Mendoza-Briceño & Erdélyi (2006) for semicircular flux tubes representing typical coronal loops of vastly different lengths (200 and 10 Mm, respectively). These studies are not directly comparable to the prominenceoriented work discussed here, because of fundamental differences in the assumed symmetries, heating pulse characteristics, and boundary conditions.…”
Section: Discussionmentioning
confidence: 94%
“…The intermittent behavior of coronal loops, and their modeling by random energy deposition representing nanoflares of locally damped wave heating, was studied by Mendoza-Briceño et al (2002 and Mendoza-Briceño & Erdélyi (2006). However, showed that the observed spiky intensity profiles due to impulsive releases of energy could also be specifically obtained from nonlinear Alfvén wave heating.…”
Section: Introductionmentioning
confidence: 99%